Glial Chloride Homeostasis Under Transient Ischemic Stress - Engels, Miriam; Kalia, Manu; Rahmati, Sarah; Petersilie, Laura; Kovermann, Peter; van Putten, Michel J. A. M.; Rose, Christine R.; Meijer, Hil G. E.; Gensch, Thomas; Fahlke, Christoph (Frontiers in Cellular Neuroscience, 2021)
High water permeabilities permit rapid adjustments of glial volume upon changes in external and internal osmolarity, and pathologically altered intracellular chloride concentrations ([Cl−]int) and glial cell swelling are often assumed to represent early events in ischemia, infections, or traumatic brain injury. Experimental data for glial [Cl−]int are lacking for most brain regions, under normal as well as under pathological conditions. We measured [Cl−]int in hippocampal and neocortical astrocytes and in hippocampal radial glia-like cells (RGL) in acute murine brain slices using fluorescence lifetime imaging microscopy with the chloride-sensitive dye MQAE. We observed substantial heterogeneity in baseline [Cl−]int, ranging from 14.0 ± 2.0 mM in neocortical astrocytes to 28.4 ± 3.0 mM in dentate gyrus astrocytes. Chloride accumulation by the Na+-K+-2Cl− cotransporter (NKCC1) and chloride outward transport (efflux) through K+-Cl− co-transporters (KCC1–KCC3) or excitatory amino acid transporter (EAAT) anion channels control [Cl−]int to variable extent in distinct brain regions. In hippocampal astrocytes, blocking NKCC1 decreased [Cl−]int, whereas KCC or EAAT anion channel inhibition had little effect. In contrast, neocortical astrocytic or RGL [Cl−]int was very sensitive to block of chloride outward transport, but not to NKCC1 inhibition. Mathematical modeling demonstrated that higher numbers of NKCC1 and KCC transporters can account for lower [Cl−]int in neocortical than in hippocampal astrocytes. Energy depletion mimicking ischemia for up to 10 min did not result in pronounced changes in [Cl−]int in any of the tested glial cell types. However, [Cl−]int changes occurred under ischemic conditions after blocking selected anion transporters. We conclude that stimulated chloride accumulation and chloride efflux compensate for each other and prevent glial swelling under transient energy deprivation.